PENGARUH ALGINAT SEBAGAI EDIBLE COATING TERHADAP KUALITAS BUAH POTONG KLIMAKTERIK: KAJIAN PUSTAKA - Armina Meikyo Puspitasari; Hermawan Seftiono (Jurnal Teknologi, 2023)
The effect of alginate on the quality of climacteric fresh cut fruits stored in refrigerator temperatures (2–5 °C) for 12–16 days was studied. The control (uncoated) and coated with alginate with various concentrations based on this study were analyzed their the physical (weight loss, texture, and color), chemical (pH, total soluble solids content, and titratable acidity), microbiological (total plate count and yeast and mold), and sensory characteristics. Weight loss and texture analysis showed that 1.5% alginate could inhibiting weight loss and maintaining hardness in fresh cut apple. Color analysis showed that 2% alginate could inhibiting °hue rate, that slowing color changes in fresh cut papaya. Analysis of pH, total soluble solids content, and titratable acidity showed that 2% alginate can maintaining pH value of fresh cut apricot, delaying of sugar utilization as substrate in respiration of fresh cut papaya, and maintaining organic acid in fresh cut kiwi. Total plate count and mold and yeast analysis showed that 1% alginate could inhibiting contamination of fresh cut watermelon and inhibiting the growth of mold and yeast in fresh cut yellow melon. Sensory evaluation analysis showed that 2% alginate could maintaining sensory characteristics in fresh cut guava. Alginate was effectively reduced respiration rate, transpiration, lowering of organic acids utilization, and inhibiting the growth of bacteria, mold and yeast until 12 days. Based on 25 studies 1.5% alginate plays a role in physical parameter (weight loss and texture). 2% Alginate plays a role in chemical parameters and 1% alginate inhibiting microorganism.